THE IMPACT OF JOB APPRAISAL AND COMPENSATION ON EMPLOYEE PRODUCTIVITY IN THE SUB-DISTRICT OFFICE SOUTH NIAS REGENCY - Jafar Syahbuddin Ritonga; Beby Suryani Fithri; Yuni Syahputri (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to examine the effect of Work Appraisal and Compensation on Work Productivity of Sub-district Office Employees Maniamolo South Nias Regency. This research includes population research which has been conducted on 30 employees at the Maniamolo Sub-District Office. The questionnaire was tested for validity and reliability before collecting data research. The test tool used in this study uses the classical assumption test which includes the data normality test, classical assumption test, and classical assumption test. Assumption test which includes data normality test, multicolonierity test, autocorrelation test, and heteroscedasticity test. The data analysis method used is multiple regression. The research resulted in the following: (1) Work Appraisal has a positive and significant effect on Employee Productivity which is indicated by the value of tcount (6.947) ttable (1.703) and a significant level of 0.000 (0.05). (2) compensation has a positive and significant effect on employee work productivity which is indicated by the value of tcount = (3.093) t table (1.703) and a significant level of 0.005 (0.05). (3) Appraisal Work Appraisal and Compensation have a joint effect on employee work productivity, which is indicated by the value of f count 41.365 3.354 significant level of 0.000 α = 0.05, and while the value of the coefficient of determination (R2) of 0.754 or 75.4%, which means that the ability of the independent variables (Work Appraisal and Compensation) can explain the dependent variable (Work Productivity Employees) is 75.4% and the remaining 24.6% is explained by other variables.Therefore it can be concluded that Job Appraisal and Compensation have a positive and significant effect on Employee Productivity.